2012
DOI: 10.1101/gad.184788.111
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine fibroblast growth factors 15/19 and 21: from feast to famine

Abstract: We review the physiology and pharmacology of two atypical fibroblast growth factors (FGFs)-FGF15/19 and FGF21-that can function as hormones. Both FGF15/19 and FGF21 act on multiple tissues to coordinate carbohydrate and lipid metabolism in response to nutritional status. Whereas FGF15/19 is secreted from the small intestine in response to feeding and has insulin-like actions, FGF21 is secreted from the liver in response to extended fasting and has glucagon-like effects. FGF21 also acts in an autocrine fashion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
412
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(422 citation statements)
references
References 139 publications
(197 reference statements)
8
412
1
1
Order By: Relevance
“…Furthermore, we observed a pronounced reduction in the level of circulating fibroblast growth factor 21 (FGF21) in fasted LKO animals (Fig. 2h), a liver-secreted hormone that has critical roles in lipid homoeostasis during starvation [27][28][29] . Given that FGF21 is a key endocrine regulator of adipocyte lipolysis 28 , this may account for, at least partially, the decreased levels of circulating FFAs in fasted LKO mice (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, we observed a pronounced reduction in the level of circulating fibroblast growth factor 21 (FGF21) in fasted LKO animals (Fig. 2h), a liver-secreted hormone that has critical roles in lipid homoeostasis during starvation [27][28][29] . Given that FGF21 is a key endocrine regulator of adipocyte lipolysis 28 , this may account for, at least partially, the decreased levels of circulating FFAs in fasted LKO mice (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Many studies have established the importance of FGF21 that functions as a hormone to regulate carbohydrate and lipid metabolism (24). Despite its remarkable pharmacological beneficial effects in improving metabolic parameters such as body weight, insulin sensitivity, and hyperlipidemia, increased circulating levels of FGF21 have been shown to be associated with human obesity, type 2 diabetes, and NAFLD (34 -40).…”
Section: Discussionmentioning
confidence: 99%
“…As a hepatokine, FGF21 expression is responsive to nutritional states (24), and animal model studies have shown that hepatic FGF21 is transcriptionally controlled by the nuclear receptor PPAR␣ FIGURE 8. XBP1s transactivates the transcriptional activity of the Fgf21 promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF21 is an atypical member of the FGF superfamily that, because of a lack of a heparin binding domain, is able to escape into the circulation, functioning as a hormone to regulate carbohydrate and lipid metabolism (20,21). In the metabolic context, FGF21 was first discovered to induce glucose uptake in 3T3L1 adipocytes (22).…”
mentioning
confidence: 99%